Biosolid compost amendment increases soil fertility and soybean growth. (10th November 2020) - Vergara Cid, Carolina; Ferreyroa, Gisele V.; Pignata, María L.; Rodriguez, Judith H.
Abstract: This study evaluates the effect of soil amendment with biosolid compost with wood shavings and yard trimmings on soil fertility, and soybean ( Glycine max ) biomass, productivity, nutrient uptake, and potential accumulation of toxic elements, like Pb. Soil from agricultural fields under intense crop production were amended with compost at 0%, 5% and 10% w/w rate, and incubated under controlled conditions before planting. Then, a greenhouse experiment was performed to study soybean growth, physiological indicators of productivity, and antioxidant response (chlorophylls, carotenes, antioxidant power, soluble sugars and proteins), as well as nutrient (Mg, Cu, Mn, and Zn), and Pb accumulation. Moreover, soil nutrient status (pH, cation exchange capacity, organic matter, nitrogen, sulfur, extractable cations, and soil microbial activity) were analyzed. The results showed that compost improved soil fertility and microbial activity, including nodulation in soybean roots. Biomass production was strongly increased; content of chlorophyll, carotenes, sugars, and protein also increased. Grains were produced only in the compost treatments. Compost addition also reduced nutrient deficiencies in leaves and grains, and Pb accumulation in soybean. Our findings contribute with information about the role of biosolid compost in sustainable agriculture: allowing the recovery of soil fertility in agricultural soils under intensive production and, consequently, improvement of crop growth.